2013
DOI: 10.3386/w18981
|View full text |Cite
|
Sign up to set email alerts
|

The Demise of Walk Zones in Boston: Priorities vs. Precedence in School Choice

Abstract: At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w18981.ack NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Echenique and Yenmez (2015) provide a characterization of strategy-proof mechanisms, which is similar to the ones by Westkamp (2013) and Kominers and Sönmez (2015). Dur, Kominers, Pathak, and Sönmez (2013) study how to control school priorities over sets of students and how to handle diversity constraints in the context of Boston school choice. Budish, Che, Kojima, and Milgrom (2010) develop a randomized mechanism which achieves a feasible assignment in expectation that satisfies type-specific ceilings.…”
Section: Related Literaturementioning
confidence: 99%
“…Echenique and Yenmez (2015) provide a characterization of strategy-proof mechanisms, which is similar to the ones by Westkamp (2013) and Kominers and Sönmez (2015). Dur, Kominers, Pathak, and Sönmez (2013) study how to control school priorities over sets of students and how to handle diversity constraints in the context of Boston school choice. Budish, Che, Kojima, and Milgrom (2010) develop a randomized mechanism which achieves a feasible assignment in expectation that satisfies type-specific ceilings.…”
Section: Related Literaturementioning
confidence: 99%
“…The precedence order of priority classes matters in the allocation procedure, as shown by Dur et al (2013) by demonstrating that a simple priority scheme might be discriminating for some groups. For instance, let us assume there are five seats with siblings and distance priority and a further five seats with only distance priority.…”
Section: Particularities Of the 2016 Systemmentioning
confidence: 99%
“…It can be done by allocating the places for siblings first and then the remaining seats or in reverse. Dur et al (2013) showed that the reverse approach can benefit children with siblings, and Hafalir et al (2013) showed that reserving places for a certain minority results in a better allocation for the minority than limiting the quota for the majority does. Under the latter policy, both groups (minority and majority) could be worse off.…”
Section: Operationalisation Of Policy Designsmentioning
confidence: 99%
See 2 more Smart Citations